2021
DOI: 10.1186/s12610-021-00140-w
|View full text |Cite
|
Sign up to set email alerts
|

Male cancer patient sperm cryopreservation for fertility preservation: 10-year monocentric experience

Abstract: Background Sperm cryopreservation, an effective method for preserving male fertility, is very advantageous for men suffering from cancer. Unfortunately, as both physicians and cancer patients are unaware of the possibilities for sperm cryopreservation, the data on evaluation of semen parameters and disposition of cryopreserved samples among Chinese cancer patients are scarce. Results Male tumours were classified into six major types, germ cell tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
(26 reference statements)
0
4
0
1
Order By: Relevance
“…Sperm quality varies with the type of underlying disease, with patients with testicular malignancy and hematological malignancies showing the lowest sperm counts ( Vomstein et al , 2021 ). However, some studies have not observed differences in sperm parameters among cancer patients ( Auger et al , 2016 ; Song et al , 2019 ; Liu et al , 2021 ). In the present study, failed-to-cryopreserve occurred in 10% (95% CI, 8–12%) of the patients.…”
Section: Discussionmentioning
confidence: 98%
“…Sperm quality varies with the type of underlying disease, with patients with testicular malignancy and hematological malignancies showing the lowest sperm counts ( Vomstein et al , 2021 ). However, some studies have not observed differences in sperm parameters among cancer patients ( Auger et al , 2016 ; Song et al , 2019 ; Liu et al , 2021 ). In the present study, failed-to-cryopreserve occurred in 10% (95% CI, 8–12%) of the patients.…”
Section: Discussionmentioning
confidence: 98%
“…Leukemia had a significant effect on sperm motility-related parameters and RRPM. Previous research demonstrated that a variety of tumors had a significant and negative impact on the quality of semen and the production of sperm in young adult men, and that patients with testicular or hematological tumors had a significantly lower SC or TSC, RRPM, and TPSA; furthermore, the lowest PR percentages were found in patients with leukemia and brain tumors [ 7 , 11 , 21 , 22 , 28 , 29 ]. According to previous findings, 38.3% of tumor patients undergoing autologous sperm preservation had normal semen quality, 7.5% had azoospermia, 57.2% had severe asthenozoospermia, 22.3% had severe oligozoospermia, and patients with TC had the lowest semen parameters [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over a follow-up period of 6 to 78 months in our bank, the proportion of subjects who used their preserved semen to undertake ART (in-vitro fertilization/intracytoplasmic sperm injection, IVF/ICSI) was 6.34%. Most previous studies reported that the use of preserved sperm ranged from 3.0% to 11.9% [ 7 , 8 , 15 , 16 , 23 , 28 , 30 , 31 , 33 , 34 ], with a few studies reporting rates as high as 17.2% to 23.2% [ 35 ]. Researchers agree that the use of cryopreserved spermatozoa was low, and that sperm freezing was an important part of the comprehensive suite of treatments for men undergoing gonadotoxic therapy; however, this strategy is under-utilized.…”
Section: Discussionmentioning
confidence: 99%
“…Однак такий природний усталений стан суспільних відносин в умовах глобалізаційних змін піддається трансформації. Зовнішні чинники змінюють буттєві атрибути соціуму, зокрема демографічна криза поєднується з перенаселенням у певних регіонах, медико-технологічні можливості подолання безпліддя не відповідають морально-етичним нормам суспільства, простежується застосування фундаменталістських та новітніх підходів до реалізації права на аборт, клонування людини, кріоконсервації статевих клітин [1], а можливість штучного запліднення потребує оновленого розуміння правового регулювання репродуктивної діяльності людини. Дисонанс проявляється й у відсутності консенсусу між правом на репродукцію і найкращими інтересами дитини, завдяки репродуктивним методикам літній батьківський вік більше не вважається серйозною перешкодою для розмноження, однак значні ризики для здоров'я майбутнього потомства приховані за успіхом репродуктивної медицини для лікування зниженої фертильності, пов'язаної з пізнім батьківством [2].…”
Section: вступunclassified